PENGARUH UKURAN DAERAH, OPINI AUDIT DAN TINGKAT KETERGANTUNGAN KEUANGAN DAERAH TERHADAP AUDIT DELAY PADA PEMERINTAH KABUPATEN/KOTA DI INDONESIA PERIODE 2015-2016 - Dewi Sarifah Tullah; Erma Apriyanti; Fitri Riyanti (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
ABSTRACK This study aims to analyze the factors that influence the length of audit delay in the Regency / City governments in Indonesia in 2015 and 2016. These factors are regional size, audit opinion and level of regional financial dependence. The population of this study is all districts / cities in Indonesia in 2015 and 2016. The study sample was determined by purposive sampling method. The data used is secondary data. The analytical method used is descriptive statistical analysis and multiple regression statistical analysis. The results showed that the size of the area did not affect audit delay. Audit opinion and the level of regional financial dependence proved to have a significant effect on audit delay. The size of the area does not affect the audit delay because many of the few accounting entities cannot determine the size of the audit delay. Audit opinion has an effect on audit delay because the area that obtains WTP opinion indicates that the region has good governance that will compile financial reports in a timely manner so as to minimize audit delay. The level of regional financial dependency influences audit delay, this is due to the higher regional financial dependence, so that the area will be more obedient to the regulations and will prepare its financial statements in a timely manner so as to minimize audit delay